2012
DOI: 10.1371/journal.pone.0035297
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Virus-Containing Compartments in Primary Human Macrophages Are Largely Inaccessible to Antibodies and Small Molecules

Abstract: HIV-1 assembly and release occurs at the plasma membrane of human T lymphocytes and model epithelial cell lines, whereas in macrophages intracellular sites of virus assembly or accumulation predominate. The origin of the intracellular virus-containing compartment (VCC) has been controversial. This compartment is enriched in markers of the multivesicular body, and has been described as a modified endosomal compartment. Several studies of this compartment have revealed the presence of small channels connecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
5
38
1
Order By: Relevance
“…Our data relating to macrophage VS-mediated transfer show that MPER-directed NAb suffer the most loss of activity, and results with 10E8 Fab and T20 suggest this is at least partially mediated by steric hindrance (28). This would be consistent with limited access of IgG to virus within the VCC (7,8), to the rapid transfer of infectious HIV-1 from the VCC to contacting T cells ( Fig. 1) (4), and with electron microscopic imaging which shows tight apposition of MDM and T cell membranes at the synaptic junction (4).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our data relating to macrophage VS-mediated transfer show that MPER-directed NAb suffer the most loss of activity, and results with 10E8 Fab and T20 suggest this is at least partially mediated by steric hindrance (28). This would be consistent with limited access of IgG to virus within the VCC (7,8), to the rapid transfer of infectious HIV-1 from the VCC to contacting T cells ( Fig. 1) (4), and with electron microscopic imaging which shows tight apposition of MDM and T cell membranes at the synaptic junction (4).…”
Section: Discussionsupporting
confidence: 68%
“…Long-lived HIV-1-infected macrophages resist viral cytopathic effects and shelter replicationcompetent virions in surface-accessible (3)(4)(5)(6), but antibody-occluding (7,8), virus-containing compartments (VCCs) (6) for several weeks (9), which strongly implicates macrophages in HIV-1 persistence (10,11). Moreover, by efficiently spreading HIV-1 to uninfected CD4 ϩ T cells through direct cell-to-cell contact (4,12), macrophages may actively contribute to viral pathogenesis (10).…”
mentioning
confidence: 99%
“…Notably, mature particles stored in macrophages remain infec-tious for weeks in the presence of a protease inhibitor (20). Moreover, viruses in VCCs are inaccessible to neutralizing antibodies (14,17) yet can be transferred to CD4 ϩ T cells that come into contact with the infected macrophages (21,22). These findings collectively support the hypothesis that VCC-associated viruses are likely to play important roles in HIV-1 pathogenesis.…”
supporting
confidence: 53%
“…In contrast, early ultrastructural studies of HIV-1-infected primary macrophages showed that both mature and immature HIV-1 particles and budding structures accumulate in intracellular compartments (10,11) which share some similarity with endosomes (5,11,12). Subsequent EM studies over the past decade revealed that at least some of these intracellular compartments, now termed virus-containing compartments (VCCs), are deep and convoluted invaginations of the PM and appear to form connections to the cell surface and extracellular space via tubular structures in a dynamic and transient manner (5,(13)(14)(15)(16)(17)(18)(19). Notably, mature particles stored in macrophages remain infec-tious for weeks in the presence of a protease inhibitor (20).…”
mentioning
confidence: 99%
“…Although the antiviral profile of antiretroviral therapy (ART) is partially defined in macrophages (2,(9)(10)(11), a direct link between potency and cellular pharmacology had not been reported. The relationship between the cellular pharmacology of ART and macrophages can impact viral loads, emergence of resistant HIV-1, and the long-term survival of infected individuals (8,12). For these reasons, understanding the dynamics of ART pharmacology in macrophages and subsequent targeted elimination of both the cells and the virus that they harbor are critical to eliminating HIV-1 infection.…”
mentioning
confidence: 99%